Pengaruh Book Tax Difference Terhadap Persistensi Laba dan Akrual (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI Tahun 2009-2012) - Resha Nofrita; Nurzi Sebrina (Universitas Negeri Padang, 2014)
This research was aimed to examine and find out empirical evidence of the influence of book tax difference on earning persistence and accrual. Sample used in which cause by this research was manufacturing firm listed in Indonesian Stock Exchange (BEI) during period 2009-2012. Total sample was 46 companies and the data was collected using purposive sampling method. The analysis of this research was panel regression analysis. The result showed that 1) firm with large positive (negative) book tax difference have less earning persistence than small book tax difference, 2) firm with large positive (negative) book tax difference do not have less accrual persistence than small book tax difference Keywords : book tax difference, earning persistence, acrual